A species of Coprococcus is related to BMI in patients who underwent malabsorptive bariatric surgery and its abundance is modified by magnesium and thiamin intake - Suárez-Sánchez, Fernando; Pérez-Ruiz, Evelyn; Ramírez-Silva, Claudia Ivonne; Molina-Ayala, Mario Antonio; Rivera-Gutiérrez, Sandra; León-Solís, Lizbel; García-Morales, Lázaro; Rodríguez-González, Arturo; Martínez-Ortiz, César; Meneses-Tapia, Luis Axiel; Cruz-López, Miguel (Frontiers in Endocrinology, 2025)
BackgroundSevere obesity is associated with metabolic alterations and an increased risk of developing type 2 diabetes. Bariatric surgery, especially malabsorptive procedures, results in significant clinical improvements and induces changes in the gut microbiota composition. This study aimed to identify bacterial taxa associated with changes in body mass index (BMI) in patients undergoing bariatric surgery and to explore their relationship with nutrient intake.MethodsIndividuals with severe obesity were recruited prior to and following bariatric surgery. Fecal DNA was extracted and the V4 region of the 16S rRNA gene was sequenced. Quality control and taxonomic classification were performed using QIIME2 and the Greengenes database. Nutrient intake was assessed through a 7-day dietary recall. Anthropometric measurements and blood samples were collected to evaluate clinical variables. Statistical analyses were conducted using R software.ResultsSignificant differences in gut microbiota diversity were observed post-bariatric surgery. The Shannon and Simpson diversity indices decreased significantly after surgery (p < 0.001). Beta diversity analysis (Bray-Curtis, Weighted and Unweighted UniFrac) also showed significant differences between pre- and post-surgery samples (p = 0.001). The abundance of a species within the genus Coprococcus was positively correlated with magnesium and thiamin intake in post-surgery patients (rho = 0.816, pFDR = 0.029 and rho = 0.812, pFDR = 0.029, respectively). Furthermore, Coprococcus sp. abundance was positive associated with BMI in pre-surgery individuals (p = 0.043) but negative associated with BMI in post-surgery individuals (p = 0.036). Several taxa within the order Clostridiales and microbial metabolic pathways involved in sugar degradation, acetate, thiamin (vitamin B1) and some amino acid production were enriched prior to surgery.ConclusionsThe abundance of a species of the genus Coprococcus showed an inverse relationship with BMI in pre-surgery and post-surgery individuals and correlated positively with magnesium and thiamin intake in patients who underwent a malabsorptive bariatric surgery. These findings suggest that optimizing micronutrient intake may enhance the beneficial effects of bariatric surgery on BMI by favorably modulating gut microbiota composition.